Toleransi Tanaman Lanskap Terhadap Pencemaran Udara di Kota Sidoarjo - Sylvia Hasna Salsabila; Pangesti Nugrahani; Juli Santoso (Jurnal Lanskap Indonesia, 2020)
Landscape plants is one of horticultural plants, wich has a few functions, such as for esthetics plant, giving shade on the road, hedges and absorbing air pollution. Judging from its existence, landscape plants are often facing problem, such as clash with air pollution, as a result of the process of photosynthesis on the plants are disrupted. This research is conducted in two locations in the city of Sidoarjo, at the Alun-alun Sidoarjo area as the control location (L0) and Aloha area as the polluted location (L1). Method to determine tolerance level through calculation of APTI (Air Pollution Tolerance Index) with parameters of leaf pH, water content, ascorbic acid and chlorophyll.